Love bears all things [large type] - Wiseman, Beth, 1962- (Wiseman, Beth, 1962- Amish secrets novel, 2016)
Could God be offering Charlotte a second chance at true love? Charlotte Dolinsky needs time to recover after breaking up with her boyfriend, Ryan. But when a surprise visitor shows up on her doorstep in Texas, she's forced to put aside her own worries to help her Amish friends in Lancaster County. Soon she is entangled in a web of deception -- and this time, she isn't the only one keeping secrets. Daniel Byler struggles each day in his Amish community to heal from his fiancée's betrayal. When he discovers that a member of his family is in danger of being shunned, his pain turns to fear. His only way to help is by partnering with Charlotte, a woman he barely knows who has already deceived them all before. Charlotte begins building a friendship with Daniel that she'll need to lean on when more surprises surface from her past and she once again finds herself torn between two worlds. Will Charlotte's friends in the Amish community be able to show her the power of redemption and lead her home? And can she help young Jacob realize that God offers second chances at happiness when she isn't even sure herself?